All Days 2014
DOI: 10.2118/167993-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Need for High-Frequency Vibration Measurement Along with Dynamics Modeling to Understand the Genesis of PDC Bit Damage

Abstract: Drilling vibration can be harmful to the bit and the bottomhole assembly (BHA), resulting in damage and tool failure and subsequent non-productive time (NPT). Bit damage while drilling offshore is costly, and any improvement in bit life can save multiple unplanned trips and lead to savings for operators. Consequently, dynamic dysfunctions have been the focus of industry research to understand and mitigate their effects. In this paper, the authors present a field case study from an offshore appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…No borehole-caliper measurement was available, but using the method in Lesso et al (2011) to examine the stabilizer positions and rate of penetration (ROP) suggested the transition was the result of two different BHA contact points entering an interval of overgauge hole. In this overgauge hole, the clearance was thought to be large enough to allow the BHA to bow out because of centripetal forces and enter into a steady state of whirl (Shyu 1989;Vandiver et al 1990). Transition out of the whirl was caused by the stabilizers moving back into an in-gauge hole.…”
Section: Case 2 Transition From Low-level Torsional Oscillationsmentioning
confidence: 99%
See 2 more Smart Citations
“…No borehole-caliper measurement was available, but using the method in Lesso et al (2011) to examine the stabilizer positions and rate of penetration (ROP) suggested the transition was the result of two different BHA contact points entering an interval of overgauge hole. In this overgauge hole, the clearance was thought to be large enough to allow the BHA to bow out because of centripetal forces and enter into a steady state of whirl (Shyu 1989;Vandiver et al 1990). Transition out of the whirl was caused by the stabilizers moving back into an in-gauge hole.…”
Section: Case 2 Transition From Low-level Torsional Oscillationsmentioning
confidence: 99%
“…Bending moment MðxÞ corresponding to vðxÞ is given by the moment-curvature relationship (Shyu 1989):…”
Section: Appendix A: Theoretical Equations For Bending Caused By Whirlmentioning
confidence: 99%
See 1 more Smart Citation
“…According to paper [7], the normal force at the wear flat (14) where l ϭ overall wear flat length: l ϭ nl n ; l n ϭ wear flat length per blade; ϭ rate of change of the contact length with depth d at small depths of cut; S ϭ normal stress acting at the cutter wear surface. The stress S may be considered permanent and approximately equal to the intrinsic specific energy e [15].…”
Section: Cutting Modelmentioning
confidence: 99%
“…In recent years downhole measurements revealed high-frequency torsional oscillations of the order of hundreds of hertz with sufficiently great amplitude [10,14]. It is considered that these oscillations propagate within the BHA for comparatively short distance.…”
Section: Introductionmentioning
confidence: 99%